Legal Study of Children with Emotional disturbance and Mental Health Needs and Implication for Practice - Dieterich, Cynthia A.; Snyder, Nicole D.; Villani, Christine J. (Journal of Law & Education, 2016)
Keywords: dept.cur; peer-reviewed

Developing as Teachers and as Researchers: Emerging Professionals' Experiences with Cooperative Inquiry - Bower-Phipps, Laura; Cruz, Maria; Albaladejo, Cristina; Johnson, Arlette; Homa, Thomas (Networks: An Online Journal for Teacher Research, 2016)
This article details the second cycle of cooperative inquiry undertaken by emerging educators who self-identify as "other" because of gender, language, ethnicity, and/or sexual orientation. The current cycle focuses on the impact participation in cooperative inquiry had on researchers' teaching practices. Data sources include transcripts of group discussions and reflective writing completed six months, eighteen months, and two years after the completion of the first cycle of cooperative inquiry. Findings suggest that as a result of engagement in cooperative inquiry, the teacher/researchers established practices to decrease isolation, build unity, and understand students' backgrounds. Teacher/researchers viewed themselves as advocates for diversity within the classroom, took a collaborative approach to teaching, and came to see research as an essential element of effective teaching.
ERIC Number: EJ1152312
Keywords: Beginning Teachers; Cooperation; Educational Practices; Elementary School Teachers; Inquiry; Minority Group Teachers; Preservice Teachers; Self Concept; Social Distance; Student Teachers; Teacher Educators; Teacher Researchers; dept.cur

Developing mentors: an analysis of shared mentoring practices - Bower-Phipps, Laura; Klecka, Cari Van Senus; Sature, Amanda L (The New Educator, 2016)
Understanding how experienced teachers share and articulate effective mentoring practices can guide efforts to prepare quality mentors. This qualitative study focused on mentoring practices within a teacher-designed student-teaching program conceptualized while the mentor teachers within the program were students in a graduate-level mentoring course and implemented upon the mentors’ completion of their graduate studies. Data sources included interviews and field notes from meetings with mentors and student teachers. The results detail specific mentoring practices: explicit instruction through scaffolding, developing the whole teacher, student-teacher-directed learning, fostering student teachers’ individual practice, explicit mentoring of one another, and reflecting on mentoring. These practices were enabled by program structures such as mentor meetings, an online forum, and mentors’ observation of all student teachers in the program. © 2016, © 2016 CCNY and ATE.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-875-982-659-553 tex.type: [object Object]
Keywords: dept.cur; peer-reviewed